Problems of Settlement of Disputes related to Trusts - N. V. Sokolova (Московский журнал международного права)
Trusts have widely spread in Europe during the last years. The Hague Convention on the Law Applicable to Trusts and on their Recognition established common conflicts of law principles on the law applicable to trusts for “trust” States and “non-trust” States alike. When trust assets, beneficiaries or trustees involve a “non-trust” State, then the question of jurisdiction of disputes arising from the trust occurs. According to international conventions signed by European States such disputes may be settled by a court of the State of the defendant’s domicile or by the court mentioned by the settler. In the USA an extrajudicial way of settlement of disputes from trusts is often used.